Effect of the fabrication condition of membrane electrode assemblies with carbon-supported ordered PtCo electrocatalyst on the durability of polymer electrolyte membrane fuel cells - Jung, Jeawoo; Park, Hyun S.; Han, Jonghee; Kim, Hyoung-Juhn; Henkensmeier, Dirk; Yoo, Sung Jong; Kim, Jin Young; Lee, So Young; Song, Kwang Ho; Park, Hee-Young; Jang, Jong Hyun (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Electrode structure improvement is one of the most promising paths for improving the durability of polymer electrolyte membrane fuel cells (PEMFCs). As strategies to prevent structural deformation and enhance the durability of membrane electrode assemblies (MEAs) with structurally ordered PtCo/C-based cathodes, we evaluated the effect of hot pressing and reinforcing the electrode's structure by increasing the ionomer content. Even though the initial performances of the hot-pressed MEA (HP) and the MEA with extra cathode ionomer (EI) were lower than that of the conventional MEA (CE) by 13.6% and 19.1%, respectively, CE degraded much more significantly than HP and EI after an accelerated degradation test. Therefore, HP and EI could deliver significantly higher single cell performances than CE (22.7% and 43.7%, respectively). The improvements in the durability of HP and EI could be correlated with the structural stability which could be evaluated by structure and electrochemical analysis including electrochemical impedance spectroscopy. (C) 2020 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.